OBSERVATIONS ON THE DISTRIBUTION AND OCCURRENCE OF DIATOMS IN THE INSHORE WATERS OF THE GULF OF MANNAR AND PALK BAY - Raghu Prasad, R; Ramachandran Nair, P V (Indian Journal of Fisheries, 2015)
From year to year qualitative and quantitative variations, as well as fluctuations of a minor nature in the regularity in appearance or disappearance of diatoms and their blooms are found in every region. As the diatoms constitute the chief components of the primary food supply of the sea, data on their occurrence, distribution pattern and fluctuations are of importance. Therefore, an attempt was made to study the nature and composition of the diatom community that occur in the plankton of Mandapam area, the abundance of species and the recurrent pattern in the annual distribution of the various species. The results are based on regular tow-net samples collected from the inshore waters of the Gulf of Mannar during January 1950 to June 1953 and Palk Bay during May 1951 to June 1953.